2009
DOI: 10.1017/s0022215109991630
|View full text |Cite
|
Sign up to set email alerts
|

Significance of fascin expression in laryngeal squamous cell carcinoma

Abstract: These results suggest that laryngeal squamous cell carcinomas with high levels of fascin expression may be more aggressive than those with low expression levels. Further studies with larger series are needed to support these results and to clarify rationales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…We found a positive correlation between high expression of fascin-1 and advanced tumor stage (T3+T4), poor cancer differentiation, N+ cancer, and advanced clinical stage (III+IV). This observation was in line with the work of Durmaz et al [18] and Zou et al [19] for LSCC and other researchers for a number of other malignant neoplasms [12], [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a positive correlation between high expression of fascin-1 and advanced tumor stage (T3+T4), poor cancer differentiation, N+ cancer, and advanced clinical stage (III+IV). This observation was in line with the work of Durmaz et al [18] and Zou et al [19] for LSCC and other researchers for a number of other malignant neoplasms [12], [14].…”
Section: Discussionsupporting
confidence: 92%
“…Fascin-1 overexpression was found associated with unfavorable prognosis in many malignant tumors such as colon cancer [11], gastric cancer [13], oral squamous cell carcinoma [14],esophageal squamous cell carcinoma (ESCC) [15], non-small-cell lung cancer (NSCLC) [16], and breast cancer [17]. Overexpression of fascin-1 was found associated with aggressiveness of LSCC but in a limited number of subjects [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, it has been reported that fascin + tumor epithelium has strong invasiveness with poorer prognosis in various carcinomas, such as ovarian, breast, pancreas, lung, cutaneous, brain, gastrointestinal, thyroid, prostate, urothelial, intrahepatic cholangiocarcinoma and skin tumors (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The significance of epithelial fascin expression has been reported to be associated with invasiveness and metastasis, since it aids in cell migration and proliferation through increases in lamellipodial and filopodial cell protrusions (15).…”
Section: Epithelium -------------------------------------------------mentioning
confidence: 99%
“…In normal adult human tissues, fascin expression is restricted to neurons and DCs; both cell types have markedly large filopodia and are highly motile (11,13). Fascin expression in various neoplastic cells has also been investigated, and its expression has been reported to be associated with epithelial to mesenchymal progression and invasion of tumor cells as well as a clinically aggressive manifestation and poorer prognosis (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, to the best of our knowledge, immunohistochemical studies for the detection of fascin + mature DCs in thymoma have yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Calponin may be a prognostic factor of laryngeal myoepithelial carcinoma [3]. Other proteins are also related to the progress of laryngeal carcinoma, such as REPP86 [4], DJ-1 [5], SATB1 [6], CRBP-1 [7], fascin [8] and Cap-43 [9]. However, few studies were performed on a systematic protein or gene level to explore the roles of these proteins in different laryngeal carcinoma progress.…”
Section: Introductionmentioning
confidence: 99%